PENGARUH KEBIJAKAN HUTANG DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN MANUFAKTUR SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sandra M Tuna; Ilyas Lamuda; Zubaidah Rahman (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
The aim of the research is to determine the impact of debt policy and dividend policy on the value of manufacturing companies in the automotive sector. The sampling method used is Purposive Sampling. The data analysis techniques employed are descriptive statistical analysis and multiple linear regression analysis. The results of the multiple linear regression equation show a constant value of -2.552, which means that the average company value decreases by 2.552 when there is no increase in Debt Policy and Dividend Policy. The regression coefficient for Debt Policy is 0.540, which means that when the Debt Policy increases by 1%, the company value will increase by 0.540, assuming the dividend policy remains constant. The regression coefficient for Dividend Policy is 0.023, which means that when the Dividend Policy increases by 1%, the company value will increase by 0.023, assuming the debt policy remains constant.